ACCOUNTING INFORMATION SYSTEMS AND THEIR QUALITY: A REVIEW ARTICLE - Kifah Sami Hussein (Scholars Digest Publishing, 2024)
Occurs related to the accounting information system and its quality. In general, it also aims to reach basically the importance of the accounting information system in the organization that they need for work tasks and work performance that directly or indirectly provides a product or service to the customer and the leaders of the organization.
Keywords: Accounting information systems, Review article concept and historical development.